Water mite species of the genus Hydrodroma Koch (Acari: Hydrachnidia, Hydrodromidae) from Australia. Part II - Pesic, Vladimir; Smit, Harry (Zootaxa, 2007)
Two new water mite species of the genus Hydrodroma Koch (Acari: Hydrachnidia, Hydrodromidae), characterized by single or absence of swimming setae on II-L-5, are reported from Australia: Hydrodroma wilesi sp. nov. and H. cooki sp. nov. New information is provided for H. tonapii Cook from India.